SUSCEPTIBILITY OF DESI AND COMMERCIAL LAYER BREEDS TO LOW PATHOGENICITY AVIAN INFLUENZA VIRUS INFECTION - F. Rasool a; Z. A. Nizamani a; N. M. Soomro a; F. Afzal b; F. Parveena; S. Rahman a (Journal of Animal and Plant Sciences, 2014)
Host resistance in Desi and commercial layer breeds was studied in this study. It was evaluated by measuring sensitivity of RBCs to LPAIV induced hemagglutination by using RBCs of two breeds and nine other avian species. Moreover, egg infectious dose 50 (EID50) along with mean death time (MDT) in embryonated eggs, intracerebral pathogenicity in day-old chicks, and intravenous pathogenicity, in four weeks old chickens, of LPAIV H9N2 in two breeds were also compared. Using same viral suspension and RBCs from various avian species including three chicken breeds, a statistically non-significant variation was found among chicken breeds, while on species level there were significant differences in H9N2 titers. The viral titer for same virus stock solution in Desi embryonated eggs was found 1011.24 EID50 / ml while in commercial layer embryonated eggs it was found to be 1011 EID50 / ml. The mean death time in Desi layer was 96.3±13.8 hours while in commercial layer it was found to be 106.6±19.3 hours. Intracerebral Pathogenicity Index (ICPI) of the virus in Desi chicken was found to be 0.213 and in commercial layer it was 0.216. Intravenous Pathogenicity Index (IVPI) of 0.137/3 was found in Desi chicken while it was 0.1/3 in commercial layer. The H9N2 infection resulted in reduction in body weight, feed intake, water intake and a rise in rectal temperature. In conclusion, the AIV H9N2 isolate was found to be of low pathogenic in nature and it produced variable pathogenicity in Desi and commercial layer breeds pointing towards a genetic basis of resistance against LPAIV infection.
Keywords: Disease resistance; LPAIV; H9N2; Avian influenza; Desi; Layer